Recent advances in the management of hepatocellular carcinoma - Sankar, Kamya; Gong, Jun; Osipov, Arsen; Miles, Steven A.; Kosari, Kambiz; Nissen, Nicholas N.; Hendifar, Andrew E.; Koltsova, Ekaterina K.; Yang, Ju Dong (Clinical and Molecular Hepatology, 2024)
Liver cancer remains a challenge of global health, being the 4th leading cause of cancer death worldwide. Hepatocellular carcinoma (HCC) is the most common type of primary liver cancer, and is usually precipitated by chronic viral infections (hepatitis B and C), non-alcoholic steatohepatitis, heavy alcohol use, and other factors which may lead to chronic inflammation and cirrhosis of the liver. There have been significant advances in the systemic treatment options for HCC over the past decades, with several approvals of both immune checkpoint inhibitors and tyrosine kinase inhibitors in patients with preserved liver function. These advances have led to improvement in survival outcomes, with expected survival of greater than 18 months, in those with sensitive tumors, adequate liver function, and those functionally fit to receive sequential therapies. Several ongoing and promising trials are now evaluating combinational strategies with novel systemic agents and combinations of systemic therapy with locoregional therapy. In view of these trials, further advances in the treatment of HCC are foreseen in the near future.